Fifty years of German-Israeli diplomatic relations: Whither the miracle of reconciliation? - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2015)
The 12th of May 2015 marks the fiftieth anniversary of the inauguration of diplomatic relations between the Federal Republic of Germany and the State of Israel. While Germany's genocide of the European Jews means that these will never be normal relations, the anniversary sees leading representatives of both countries lauding the almost miraculous bond of trust and close web of contacts that have grown between them. And indeed, with no other country in the Middle East is Germany so closely associated. Nevertheless, reconciliation has remained largely a project of the elites, and the two societies are currently growing apart rather than together. Also, differences over a two-state settlement to the Israeli-Palestinian conflict are casting a heavy shadow over the relationship. Germany's political elite and society should therefore take the anniversary as an occasion to reflect on the meaning of Germany's historical responsibility and the implications for its policy towards Israel. (SWP Comments)
Keywords: 320